Mix design of durable concrete with the additions of silica fume or fly ash - Renato Iovino; Emanuele La Mantia (Vitruvio: International Journal of Architectural Technology and Sustainability)
The aim of the research is the laboratory study of a durable concrete, according to UNI-EN 206-1 and 11104, comparing four types of concrete by varying the type of binder to highlight some aspects of durability. For each type of concrete, to graph the correlations between: W/C ratio - resistance; cement dosage - strength; days of ripening-resistance; three mixes were packaged by varying the W/C ratio and the cement dosage. Three durable concretes were then designed, by way of example, with resistance class C30/37, exposure class XS1, workability class S5, maximum diameter 20 mm, by varying the type of binder to enhance some aspects of durability: